Evdoxios Doxiadis, State, Nationalism and the Jewish Communities of Modern Greece - Patrikiou, Alexandra (Historein, 2019)
Review of Evdoxios Doxiadis, State, Nationalism and the Jewish Communities of Modern Greece. London: Bloomsbury, 2018. 251 pp.